The Fourth Branchial Complex Anomaly: A Rare Clinical Entity. (7th December 2011) - Patel, Alpen B.; Hinni, Michael L.
Abstract : Fourth branchial pouch anomalies are rare congenital disorders of the neck and are a consequence of abnormal development of the branchial apparatus during embryogenesis. Failure to appropriately recognize these anomalies may result in misdiagnosis, insufficient treatment, and continued recurrence. Here, we present an unique presentation of two cases, describe their diagnosis, clinical course, and management, and review the literature regarding these interesting anomalies.